Virtues for the People Aspects of Plutarchan Ethics - Roskam, Geert (Leuven University Press, 2011)
Plutarch of Chaeronea was by no means an armchair philosopher. He believed in the necessity for a philosopher to affect the lives of his fellow citizens. That urge inspired many of his writings to meet what he considered people's true needs. Although these writings on practical ethics illustrate in various ways Plutarch's authorial talents and raise many challenging questions (regarding their overall structure, content, purpose, and underlying philosophical and social presuppositions), they have attracted only limited scholarly attention.Virtues for the People's collected essays deal with these questions from different perspectives and throw a new light upon this multifaceted domain of Plutarch's thinking and writing. Special points of interest are the concept of 'popular philosophy' itself and its implications, its dependence on a more theoretical philosophical background, and the importance of moral progress, the therapy of wickedness, and the common experiences of everyday life.